Detection of gravitational frame dragging using orbiting qubits. (27th April 2016) - Lanzagorta, Marco; Salgado, Marcelo
Abstract: In this paper we propose information theoretic and interferometric techniques to detect the effect of gravitational frame dragging on orbiting qubits. In particular, we consider the Kerr spacetime geometry and spin- 1 2 qubits moving in equatorial circular orbits. We ignore the  ( ℏ ) order effects due to spin–curvature coupling, which allows us to consider the motion of the spin- 1 2 particles as Kerr geometry geodesics. We derive analytical expressions for the infinitesimal Wigner rotation and numerical results for their integration across the length of the particle's trajectory. To this end, we consider the bounds on the finite Wigner rotation imposed by Penrose's cosmic censorship hypothesis. Finally we propose how the Wigner rotation strictly due to frame dragging could be observed using interferometry and other quantum metrology techniques.